2013
DOI: 10.1088/1751-8113/46/30/305302
|View full text |Cite
|
Sign up to set email alerts
|

Area law for random graph states

Abstract: Abstract. Random pure states of multi-partite quantum systems, associated with arbitrary graphs, are investigated. Each vertex of the graph represents a generic interaction between subsystems, described by a random unitary matrix distributed according to the Haar measure, while each edge of the graph represents a bi-partite, maximally entangled state. For any splitting of the graph into two parts we consider the corresponding partition of the quantum system and compute the average entropy of entanglement. Firs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The probability distributions on D d we have considered so far do not make any assumptions on the internal structure of the underlying Hilbert space C d . To address this issue, in [CNŻ10,CNŻ13] the authors introduce and study a new family of ensembles of density matrices, called random graph states, which encode the underlying structure of the Hilbert space. We introduce next these distributions, referring the interested reader to [CNŻ10,CNŻ13] for the details.…”
Section: Entanglement Of Random Quantum Statesmentioning
confidence: 99%
See 3 more Smart Citations
“…The probability distributions on D d we have considered so far do not make any assumptions on the internal structure of the underlying Hilbert space C d . To address this issue, in [CNŻ10,CNŻ13] the authors introduce and study a new family of ensembles of density matrices, called random graph states, which encode the underlying structure of the Hilbert space. We introduce next these distributions, referring the interested reader to [CNŻ10,CNŻ13] for the details.…”
Section: Entanglement Of Random Quantum Statesmentioning
confidence: 99%
“…It was shown in [CNŻ13] that the area law holds exactly for adapted marginals of graph states, where we allow arbitrary dimensions of subsystem. Note that, for a given (boundary) edge {i, j}, we have d i = d j , the common dimension of the maximally entangled state corresponding to the edge {i, j}.…”
Section: Entanglement Of Random Quantum Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, the notion of an area for some graph is not so obvious and one has to specify an appropriate definition. It has been shown that random graph states generally satisfy an area law on average [56]. For the present case, a possible way out can be achieved by probing the geometry of the region in terms of a given test particle at thermal equilibrium [57,58].…”
Section: Self-similar Ramificationsmentioning
confidence: 94%